Η πρόσληψη του "σκυλάδικου" στην Κύπρο - Πουλλή, Αρίστη (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2015)
Identity, Cultural symbols, Emotions, Cyprus
Keywords: Identity; Emotions; Cultural symbols; Cyprus; Σκυλάδικο; Ταυτότητα; Συναισθήματα; Πολιτισμικά σύμβολα; Κύπρος